Impact of immune modulation with anti–T-cell antibodies on the outcome of reduced-intensity allogeneic hematopoietic stem cell transplantation for hematologic malignancies - Soiffer, Robert J. (American Society of Hematology, 2011)
The success of reduced intensity conditioning (RIC) transplantation is largely dependent on alloimmune effects. It is critical to determine whether immune modulation with anti–T-cell antibody infusion abrogates the therapeutic benefits of transplantation. We examined 1676 adults undergoing RIC transplantation for hematologic malignancies. All patients received alkylating agent plus fludarabine; 792 received allografts from a human leukocyte antigen-matched sibling, 884 from a 7 or 8 of 8 HLA-matched unrelated donor. Using Cox regression, outcomes after in vivo T-cell depletion (n = 584 antithymocyte globulin [ATG]; n = 213 alemtuzumab) were compared with T cell– replete (n = 879) transplantation. Grade 2 to 4 acute GVHD was lower with alemtuzumab compared with ATG or T cell– replete regimens (19% vs 38% vs 40%, P < .0001) and chronic GVHD, lower with alemtuzumab, and ATG regimens compared with T-replete approaches (24% vs 40% vs 52%, P < .0001). However, relapse was more frequent with alemtuzumab and ATG compared with T cell–replete regimens (49%, 51%, and 38%, respectively, P < .001). Disease-free survival was lower with alemtuzumab and ATG compared with T cell–replete regimens (30%, 25%, and 39%, respectively, P < .001). Corresponding probabilities of overall survival were 50%, 38%, and 46% (P = .008). These data suggest adopting a cautious approach to routine use of in vivo T-cell depletion with RIC regimens.